Restrukturisasi Peta Proses Bisnis Birokrasi Pasca Pemberlakuan Undang-Undang Nomor 2 Tahun 2024 tentang Provinsi Daerah Khusus Jakarta - Zulmasyhur Zulmasyhur (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
This study aims to analyze the strategies for restructuring the bureaucratic Business Process Map (Probis) within the Jakarta Provincial Government in response to the mandate of this new law. Through the lens of Hybrid Governance and Digital-Era Governance theories, this study examines how changes in the macro-level functions of the region are adapted into the microstructure of civil service operations. This study employs a qualitative approach using an explanatory case study strategy. Data were collected through in-depth interviews with the Probis drafting team of the DKI Jakarta Provincial Government, analysis of regulatory documents, and observation of drafts of the new institutional structure. The research findings indicate that the post-DKJ Law restructuring of Probis successfully broke through rigid hierarchical deadlocks and silo mentalities through the establishment of Semi-Autonomous Decentralization Units as hybrid collaborative nodes and the automation of cross-sectoral business process integration. This reform shifts the organizational focus from a functional-centric approach to an agile, value-centric one centered on service delivery. However, challenges such as cultural resistance, sectoral ego, and inconsistencies in secondary regulations remain major structural obstacles. This study makes a theoretical contribution by proposing a Semi-Autonomous Decentralization Model for the Megacity Region as a form of institutional adaptation and a blueprint for inclusive governance of local bureaucracy in megacities following the capital relocation.